Application of Phenolic Extraction Strategies and Evaluation of the Antioxidant Activity of Peanut Skins as an Agricultural By-product for Food Industry - Kumar, S. P. Jeevan; Chintagunta, Anjani Devi; Reddy, Y. Mohan; Kumar, Ashutosh; Agarwal, Dinesh K.; Pal, Govind; Simal-Gandara, Jesus (Food analytical methods, 2021)
Peanuts are globally cultivated and more than 66.66% of the total production is utilised for oil production, while one-third is either consumed as nut or used in production of peanut butter and other snacks. The peanut processing industries reject large portions of peanut biomass in the form of peanut meal, skins and hulls, which are rich in proteins, phenolics and fibres. Efficient use of peanut skins that are rich in bioactive compounds and antioxidant activity for bio-fortification of foods and dietary supplements is in demand. In the present study, four varieties of peanuts (K-6, K-9, TMV-2 and TAG-24) which are widely cultivated in India were chosen and deduced the proximate analysis. Besides, extraction of total phenolic content (TPC) resulting in seed coat of examined peanut varieties revealed the higher phenolics content in K-9 (60.6 ± 3.0 mg/g) > K-6 (59.4 ± 1.30 mg/g) > TMV-2 (58.4 ± 1.35 mg/g) in the solvent system containing acetone:water:acetic acid at 70:29.8:0.2 ratio, respectively. In addition to K-9, K-6 showed significant antioxidant activity with lower electrical conductivity (an indicator of seed coat intactness) in comparison to the other peanut varieties. Moreover, FTIR analysis confirmed the presence of phenols, amides, esters, amino acids, carboxylic acids, alcohols and flavonoids in the seed coat of different peanut varieties. HPLC analysis further confirmed the presence of wall-bound phenolics, viz., protocatechuic acid, 4-hydroxybenzoic acid, vanillic acid, p -coumaric acid and t -ferulic acid in the skins of various peanut varieties. Owing to the presence of bioactive compounds and antioxidant activity, the peanut skins can be used for bio-fortification of food, dietary supplements, nutraceuticals, cosmetic industries and other value-added food materials. Graphical abstract